Perlindungan Konsumen terhadap Barang Rusak dengan Biaya Perlindungan dalam Platform E-commerce: Analisis Hukum Perdata Islam - Asti, Mulham Jaki; Farhan, Muh (Universitas Islam Negeri Alauddin Makassar, 2026)
This study examines the issue of legal protection for consumers against damaged goods that are still subject to protection fees on e-commerce platforms from the perspectives of positive law and Islamic jurisprudence (fiqh muamalah). The problem arises from the practice in which consumers, despite paying additional product protection fees, often face difficulties in obtaining compensation when the goods received are defective or not in accordance with the agreement. This research aims to analyze the forms of legal protection provided under Indonesian legislation, particularly Law Number 8 of 1999 concerning Consumer Protection and regulations governing electronic commerce, while also assessing the practice based on the principles of fiqh muamalah such as justice (al-‘adl), the prohibition of gharar (uncertainty), the prohibition of tadlis (fraud), and the concept of khiyar (option rights). The study employs a normative juridical method using statutory and conceptual approaches and adopts a comparative analysis between positive law and Islamic law. Data were collected through library research involving primary, secondary, and tertiary legal materials. The findings indicate that under positive law, consumers are entitled to accurate information, compensation, and legal remedies; however, the regulation concerning product protection fees is not specifically governed, resulting in gaps in its implementation. From the perspective of fiqh muamalah, the imposition of protection fees is permissible as long as it upholds transparency, contractual clarity, and fairness, and does not contain elements of uncertainty or injustice. Therefore, regulatory strengthening and harmonization between positive law and Islamic principles are necessary to ensure fairer, more certain, and more effective consumer protection in e-commerce transactions.